Prosedur Akuntansi Penerimaan Kas Pada CV GAD Production - Chery Afrenza; Yudas Tadius Andi Candra (JURNAL RISET MANAJEMEN (JURMA), 2023)
Cash receipts are cash received by the company in the form of cash for cash sales, settlement of receivables, and other transactions that can add to the company's cash. CV GAD Production in running its business in the field of event equipment provider rental requires a good cash receipt system. This study aims to determine whether the cash receipts accounting procedures at CV GAD Production have been going well. The research method used in this study is a qualitative descriptive analysis method. The results of this study indicate that in general it is quite good but there are still deficiencies. The results of this study are expected to provide input in controlling cash receipts procedures.